(untitled) (The Pakistan Development Review, 2007)
Water is one of the basic necessities of life. God has gifted Pakistan with abundant water resources, with rivers flowing down the Himalayas and Karakoram heights from the world’s largest glaciers and free and unique bounty for this land. Pakistan is basically an agrarian economy. Out of its total geographical area of 79.61 million hectares, cultivated area is 22.05 million hectares. The total area under irrigation is 19.02 million hectares [Agricultural Statistics of Pakistan (2005-06)]. Irrigated land supplies more than 90 percent of agricultural production and most of the country’s food. Agriculture sector is regarded as the backbone of Pakistan’s economy. It contributes 25 percent of the GDP. About more than 50 percent labour force is employed in this sector. Agriculture sector is also the major user of water and its consumption will continue to dominate water requirement. Similarly, for industrial development main source of energy is hydropower which is generated by dint of water stored in big dams and reservoirs. Therefore the importance of the water for the survival of our economy cannot be denied.